The Impact Analysis of the Construction of the Indrapura - Kisaran Toll Road in Asahan Regency - Pratama, Lucky Satria; Tarmizi, Hasan Basri; Sari, Raina Linda; Silalahi, Amlys Syahputra (Journal of Ecohumanism, 2024)
This study investigates the impact of toll road construction on society, with economic, social, and environmental variables. Using interview methods and questionnaires to 398 respondents in seven affected sub-districts, the data collected was analyzed using the Smart-PLS (Partial Least Square) and Analytic Network Process (ANP) methods. The results of the study show that the construction of toll roads has a significant positive impact on economic and social aspects, while the impact on environmental aspects is negative but not significant. The construction of toll roads also increases job opportunities and income for the surrounding community. Based on the hypothesis, economic and social aspects have a positive effect on the impact of development, while environmental aspects show a negligible negative influence. In conclusion, the construction of the Indrapura-Kisaran toll road brings significant economic and social benefits to the people of Asahan Regency, although more attention is needed to the environmental impact caused.